Application of Iterative Technique (IT) Using SPT N-Values and Correlations for Analysis of Tip and Shaft Capacity for an Axially Loaded Pile in Sand - Ab. Malik, Rosely (Universiti Putra Malaysia Press, 2000)
This is a theoretical method on how to analyze the axial capacity (tip and shaft) of a single pile using iterative technique on SPT-N values and SPT-N correlation. This technique allows the engineer who conducts the analyses to control the input and output information of the analyses in a systematic and organized fashion. This method is also very helpful especially for the development of pile capacity prediction using reliability method. Research on the subject is being carried out at Universiti Putra Malaysia (UPM).